A process evaluation of a shared leadership model in an intensive care unit : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Turner, Clare Lynette Eden (Massey University, 2001)
Shared leadership has been touted in the United States and United Kingdom as a model of staff management that fosters active involvement of staff, in this case nurses as experienced professionals, in patient management. This study uses process evaluation for the examination of a shared leadership model in an intensive care environment following a period of significant change and restructuring. The model was based on the shared leadership literature (porter-O'Grady, 1992) which focuses on clinical practice as a key accountability and on decentralised clinical leadership at the point of service. The model aligned with the skill acquisition framework used by the employer organisation called the Professional Development Programme (PDP). This programme aims at enhancing the development of expertise in clinical practice and supports the principles of shared leadership. This research study was undertaken to evaluate the process of implementation of the model and to discover whether there is evidence nurse involvement in the management of patient care. The results are based on the responses of 104 registered nurse respondents (56%) working in the intensive care unit of a specialised hospital. Documentation was also examined for evidence of nursing input into indirect patient management process development. The results indicate that nurses are becoming more settled in their working environment and feel more confident in their ability to provide an active role in the management of their patients within a multidisciplinary team.
Keywords: Administration; Intensive care units; Intensive care nursing